Effect of Dictation on Upper Basic Education Students’ English Language Writing Skill in Billiri LGA, Gombe State - Bega, H. Joseph.; Moses, D. Hassan; Molta, M. Gerson (Kashere Journal of Education, 2022)
This study was on the effects of dictation on upper basic education students’ English language writing skill in Billiri LGA, Gombe state. The study was guided by two research questions and the quasi-experimental research design involving two groups (Dictation and the other Non-Dictation) was used. The population of the study comprised upper basic education students of public Secondary Schools in Billiri LGA from a sample of 127 students from two intact classes selected by the simple random sampling technique to participate in the study. One validated instrument tagged: Upper Basic Education Dictation Writing Skill Test (UBEDWST) with reliability coefficient of 0.81 was used to collect data. The research questions were answered using the mean and standard deviation statistics and computed by the aid of the Statistical Packages for Social Sciences (SPSS version 23). The results obtained showed students exposed to dictation had improved spelling ability and achieved more in writing skill. The study concluded that dictation can positively influence Upper Basic Education Students’ Spelling and writing skill. The study recommended that Upper Basic Education students should be introduced to dictation activities in English language classrooms by their teachers to enhance their spelling ability and texts formation. Also, teachers of English language should make dictation a basic part of their teaching of writing and essay development. The paper recommends that teachers of English language should adopt dictation strategies such as dicto-comp and split dictation by exposing their students to interact and discover ways of constructing different sentences.